Sociodemographic profile and Psychiatric diagnosis in attempted suicide (Journal of Psychiatrists' Association of Nepal, 2017)
Introduction: The presence of a mental disorder is an important risk factor for suicide. Attempted suicide is one of the major emergencies in psychiatry. Suicide attempts are considered to be the best predictors of an eventual completed suicide. Data of patients presenting with attempted suicide is scanty in Nepal.Objective: The aim of the study was to explore the socio-demographic and psychiatric diagnosis of the patients with suicidal attemptMethod: The study population included those patients who were admitted and being managed for attempted suicide and brought for psychiatric evaluation during the period of one year (1st July 2015- 30 June 2016) at Devdaha Medical College and research institute, Nepal. Each patient underwent a detailed psychiatric evaluation by a consultant psychiatrist once they were medically stable. Details including socio-demographic data, psychiatric diagnosis, was tabulated and analyzed using SPSS-16.Result: Among the total patients (N=75), 68% were in the age group 20-39 years. Majority of the cases were female (78.7%). 53.3% cases were married and majority were from Hindu religion. Most common method of attempted suicide was by poisoning and was by intake of Organophosphorous. Adjustment disorder(44%) and Depression(24%) were the most common psychiatric diagnosis. Marital dispute (22.7%) and family dispute (17.3%) and were the most common psychosocial precipitant.Conclusion: Attempted suicide is widely prevalent on younger age group. It is usually by poisoning and the use of Organophosphorus compound is most common in our setting and is commonly associated with adjustment disorder. Hence, psychiatric care is essential for these patients.